Pengaruh Kombinasi 2,4-D Dan Bap Terhadap Induksi Kalus Eksplan Daun Dan Batang Tanaman Binahong (Anredera cordifolia (Ten.) Steenis) Secara In Vitro - Mardini, Ucik; , Triastuti Rahayu, S.Si, M.Si (2015)
Binahong (Anredera cordifolia (Ten.) Steenis) is a medicinal plant, which is very potential to be developed. Its secondary metabolite contents, namely: flavonoid, alkaloid, tannin, saponin, steroid, polifenol, triterpenoid and essential oil. Secondary metabolites can be extracted from callus through plant tissue culture. Callus culture can produce more various secondary metabolites. The objective of this research is to investigate the callus growth of binahong plant with combination of growth regulators of 2,4-D and BAP on various concentrations. This research used the completely randomized design with 2 factors, namely: 1) explants type: binahong leaves (E1) and binahong stems (E2), and 2) combination of growth regulators: combination of 2.4-D 1.5 ppm + BAP 1 ppm (Z1); and combination of 2.4-D 1.5 ppm + BAP 1.5 ppm. The result of research shows that the combination of concentration of 2.4-D and BAP has an effect on the in vitro induction of leave and stem explant callus of Binahong plant. The combination of concentration of 2.4-D 1.5 ppm, and BAP 1.5 ppm is the most optimal combination of concentration for time of callus occurrence and callus size on the stem explants. The callus produced has greenish white colors on the leave explants and white colors on the stem explants. The texture of leave and stem explants callus is crumb.